2020
DOI: 10.3390/agronomy10010070
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Appropriate Cultivar of Basil (Ocimum basilicum) Can Increase Water Use Efficiency under Water Stress

Abstract: Drought is one of the major yield constraints of crop productivity for many crops. In addition, nowadays, climate change creates new challenges for crop adaptation in stressful environments. The objective of the present study was to determine the effect of water stress on five cultivars of basil (Mrs Burns, Cinnamon, Sweet, Red Rubin, Thai) and whether water use efficiency (WUE) can be increased by using the appropriate cultivar. Water stress affected the fresh and dry weight and also the partitioning of dry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 30 publications
(63 reference statements)
10
46
0
1
Order By: Relevance
“…Basil is sensitive to drought stress, a meaningful reduction in the fresh and dry matter yield, essential oil content, chemical constituents such as proline content, carbohydrate content and protein have been reported in former studies. [29,30] Kalamartzis et al [31] found that basil cultivars should have higher water use efficiency in semi-arid regions, which allow them to save more water resources. Its dry products of the stems usually harvest at 1.2-2 (fresh weight 8-10) t/ha.…”
Section: Basil Occurrence Cultivation Classification and Variation mentioning
confidence: 99%
“…Basil is sensitive to drought stress, a meaningful reduction in the fresh and dry matter yield, essential oil content, chemical constituents such as proline content, carbohydrate content and protein have been reported in former studies. [29,30] Kalamartzis et al [31] found that basil cultivars should have higher water use efficiency in semi-arid regions, which allow them to save more water resources. Its dry products of the stems usually harvest at 1.2-2 (fresh weight 8-10) t/ha.…”
Section: Basil Occurrence Cultivation Classification and Variation mentioning
confidence: 99%
“…The genus Ocimum is characterized by great variability in both morphological characteristics and chemical composition, as evidenced by numerous cultivars and chemotypes with different growth, yield, and raw material quality characteristics [1][2][3]. Among the number of species in genus, Ocimum basilicum L. (basil) has been the most often used, primary as a culinary herb, then in the cosmetic industry and as an ornamental plant [1].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Kalamartzis et al [49] determined the effect of water stress on five cultivars of basil (Mrs Burns, Cinnamon, Sweet, Red Rubin, Thai) were found to be within the ranges of 378.5-4357.5 g m −2 for fresh herb, 65.8-922.5 g m −2 for dry herb. In addition, Karaca et al [36] determined that fresh herb yield and dry herb yield of nine basil genotypes were found to be within the ranges of 195.00-383.99 g plant −1 , 22.21-46.85 g plant −1 , respectively.…”
Section: Resultsmentioning
confidence: 95%